Implementing the UN Global Compact: role of the law of contract in promoting sustainability in international supply chains - Mboya, Meshack Kathama (Department of Commercial Law, 2018)
This paper analyses the need for multinationals to adopt and fully implement the UN Global Compact principles in their operations by influencing sustainability down their international supply chains. This analysis is premised on the various theories supporting the adoption of sustainable business practices by businesses in terms of labour, human rights, environmental responsibility and anti-corruption. The objective of the analysis is to propose the applicable law of contract tools that the multinationals can use to implement their sustainability commitments down international supply chains. Since the supply chain partners of these multinationals are distinct entities operating independently and only dealing with the multinationals through contracts, the paper proposes that sustainability can be influenced through the use of such contracts. In this, the paper appraises conditions precedent and express contractual terms as the law of contract tools that can best be utilized by multinationals in influencing supply chain sustainability. The paper shows that these tools can be utilized to guarantee that supply chain partners operate sustainably and in a manner that implements the sustainability commitments of the focal firm - the multinational. Against the background of the already existing systems, this study illustrates that the proposed tools can be used to strengthen the existing systems and especially the use of supplier codes of conduct. It also demonstrates that the effective use of these tools guarantees the adoption of sustainable practices and systems that eventually make the entire supply chain sustainable. The paper concludes that the use of these tools will guarantee the implementation of sustainability commitments, as based on the UN Global Compact, in international supply chains.